PALEOMAGNETIC PALEOLATITUDES FOR UPPER DEVONIAN ROCKS OF THE OMOLON MASSIF, NORTHEASTERN RUSSIA - Kolesov E.; Stone D.B. (My University, 2002)
The Omolon massif in northeastern Russia forms the core of the Kolyma-Omolon superterrane. The massif has an early Precambrian crystalline basement and is surrounded by the Paleozoic shelf deposits of the Omulevka terrane and various other terrane fragments. Geologic models range from the superterrane being a fragment of the Siberian craton that rifted away in late Precambrian time and traveled several tens of degrees to the south relative to the craton, to models that never allow it to move very far (of the order of 500 km) from Siberia. To test the various hypotheses, paleomagnetic data were obtained from a suite of volcanic rocks of Late Devonian age (Famennian) from the Omolon massif. These results pass fold (Ks/Kg = 3.5), reversal, and conglomerate tests. The combined data (N = 44) give a paleolatitude of 30.3° ±4.5°, and a virtual geomagnetic pole located at latitude 20.6°N and longitude 224.0°E. When compared with poles of the same age from the Siberian platform, this result indicates that the massif could have been in roughly its present position, although rotated about a vertical axis, with respect to the Siberian platform in Devonian time. This assumes that both the Siberian platform and the massif were in the same (northern) hemisphere. Additional paleomagnetic data for the Kolyma-Omolon superterrane selected from the literature indicate that in post-Devonian time, the Kolyma-Omolon superterrane was farther south with respect to the Siberian platform, and subsequently drifted back north to its present location in Jurassic time.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская